Root Causes of Brake Caliper Problems as A Corrective Action in Front of LH: A Case Study in Manufacturing Industry - Aisyah, Siti; Huwae, Priskila Timaha; Debora, Fransisca; Jaqin, Choesnul; Sitorus, Tosty Maylangi (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2024)
The industrial sector is the backbone of the country in building the defense sector and economic stability that needs to maintain productivity and be competitive. One of the companies that manufacture automotive components, Mitsubishi, manufactures automotive components and must have zero defect requirements. However, in practice, it was found that 1 (one) unit of CJM had a brake caliper malfunction in the condition that the unit was ready to be sent to the carpool consumer of a company that produces automotive components. The damage is a discrepancy in the diameter of the piston seal, which closes the gap between the piston and the piston housing, allowing for brake fluid leakage, which affects the "zero defect" commitment. Through the application of the Root Cause Corrective Action (RCCA) method with the formation of a Root Cause Investigation (RCI) team, an investigation was carried out to find the root cause of the failure. However, the data processing results of the diameter of the seal thickness obtained have a Cp value of 0.98 and a Cpk of 0.81, which means the process has not been able to work optimally. Therefore, we decided to make some improvements, adding Standard Operating Procedures (SOP), Work Instructions (WI), and making Poka-Yokes as corrective actions in dealing with this problem. After almost 3 months since the investigation began, the data processing results on the piston seal were Cp = 1.86 and Cpk = 1.80.